Responses of B-type natriuretic peptide (BNP), mature BNP and proBNP to sacubitril/valsartan differs between responders and non-responders - Hiroyuki Takahama; Toshio Nishikimi; Yasuaki Nakagawa; Naoto Minamino; Koh Ono; Kenji Moriuchi; Shoichi Miyamoto; Takahiko Kanamori; Hideaki Inazumi; Hiromu Yanagisawa; Hideaki Kinoshita; Yusuke Tamamura (Open Heart)
Background Earlier studies showed that measured changes in plasma B-type natriuretic peptide (BNP) levels are inconsistent after sacubitril/valsartan administration. The reason remains unknown but may reflect the fact that BNP immunoreactivity measured with commercial BNP assays (BNPcom) includes both mature BNP and proBNP, and neprilysin degrades only mature BNP. In addition, the responsiveness to sacubitril/valsartan varies among patients with heart failure. We investigated the mechanism underlying the inconsistency of BNP measurements after sacubitril/valsartan.Methods We measured plasma mature BNP, proBNP and total BNP (mature BNP+proBNP) levels with our immunochemiluminescent assay as well as NT-proBNP, A-type natriuretic peptide (ANP) and BNPcom with conventional assays in 54 patients with heart failure, before (baseline) and after 2, 4, 8 and 12 weeks of sacubitril/valsartan administration. Responders were defined as having NT-proBNP levels at <70% of baseline after 12 weeks.Results Among all patients, total BNP and BNPcom did not change with sacubitril/valsartan treatment, whereas NT-proBNP and proBNP decreased, mature BNP modestly increased and ANP greatly increased. Responders (n=31) exhibited smaller %changes in all natriuretic peptide levels than non-responders (n=23; all p<0.01). Receiver operating characteristic curves analysis to assess the ability of the %change in each natriuretic peptide at 4 weeks to detect responders showed that the area under the curve was about 0.80 for each peptide. There were good correlations between plasma natriuretic peptides levels at baseline and throughout the sacubitril/valsartan administration.Conclusion These results suggest that the magnitude and direction of change in each BNP form depends on its substrate specificity for neprilysin, that differences in plasma levels of each BNP form between responders and non-responders appear early and persist and that BNPcom levels at 4 weeks can be applicable to prediction of the responders. Notably, our findings show that the idea that BNPcom cannot be used as a marker of heart failure after sacubitril/valsartan should be reconsidered.